Academic Supervision by School Principals on Learning Tools in Border Areas, West Kalimantan - Agustinus Marjun; Atrianus Toni; Alexander Andi Kurnianto (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: This research delves into the academic supervision in Ketungau Hulu sub-district, Sintang Regency, West Kalimantan. The study employed descriptive methodology, encompassing interviews and questionnaires. Data was gathered from 3 out of 10 junior high schools situated in proximity to the border. 3 principals and 3 teachers were interviewed, with 25 teachers participating in the survey. Based on data analysis, 90% completion rate for resources, 77.33% for resources, below 90% for teacher guides and schedules. Principals effectively supervised academics (above 90% completion rate) and created supervision schedules (88% completion rate). Room for improvement in academic supervision tools, currently at 89.33% completion rate. Based on interviews, academic supervision varies based on teachers' readiness. Educators reduce apprehension by being familiar with supervision. Teachers adapt to technological constraints by using basic media. Teachers and principals collaborate post-supervision to address issues. Some teachers participate in MGMP activities, while financial and geographical constraints limit others. Principals' supervision planning needs enhancements for consistent oversight. Overcoming obstacles like technological limitations is crucial. Post-supervision evaluations and follow-up procedures are effectively executed. More effort is needed to ensure all teachers have training opportunities to enhance their competencies. Keywords: Academic Supervision, Principal, Education, Learning Device, Border Region